(untitled) (Journal of the College of Basic Education, 2022)
Six phenol-degrading bacterial isolates were isolated from the industrial waste water of the Doura refinery and diagnosed using the Vitek 2 System device. Its number is 262 × 105 U.M./ml when grown on phenol as the only source of carbon and energy.